Expanding the molecular versatility of an optogenetic switch in yeast - Figueroa, David; Baeza, Camila; Ruiz, Diego; Inzunza, Claudia; Romero, Andrés; Toro, Rodrigo; Salinas, Francisco (Frontiers in Bioengineering and Biotechnology, 2022)
In the budding yeast Saccharomyces cerevisiae, the FUN-LOV (FUNgal Light Oxygen and Voltage) optogenetic switch enables high levels of light-activated gene expression in a reversible and tunable fashion. The FUN-LOV components, under identical promoter and terminator sequences, are encoded in two different plasmids, which limits its future applications in wild and industrial yeast strains. In this work, we aim to expand the molecular versatility of the FUN-LOV switch to increase its biotechnological applications. Initially, we generated new variants of this system by replacing the promoter and terminator sequences and by cloning the system in a single plasmid (FUN-LOVSP). In a second step, we included the nourseothricin (Nat) or hygromycin (Hph) antibiotic resistances genes in the new FUN-LOVSP plasmid, generating two new variants (FUN-LOVSP-Nat and FUN-LOVSP-Hph), to allow selection after genome integration. Then, we compared the levels of light-activated expression for each FUN-LOV variants using the luciferase reporter gene in the BY4741 yeast strain. The results indicate that FUN-LOVSP-Nat and FUN-LOVSP-Hph, either episomally or genome integrated, reached higher levels of luciferase expression upon blue-light stimulation compared the original FUN-LOV system. Finally, we demonstrated the functionality of FUN-LOVSP-Hph in the 59A-EC1118 wine yeast strain, showing similar levels of reporter gene induction under blue-light respect to the laboratory strain, and with lower luciferase expression background in darkness condition. Altogether, the new FUN-LOV variants described here are functional in different yeast strains, expanding the biotechnological applications of this optogenetic tool.